Skrining dan Karakterisasi Parsial Senyawa Antifungi dari Actinomycetes Asal Limbah Padat Sagu Terdekomposisi - Alimuddin Ali (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Actinomycetes are one of the most attractive sources of antibiotics and other biologically active substances of high commercial value. Actinomycetes have proved to be capable of biosynthesizing secondary metabolites bearing conspicuous structural diversity, which could be further enlarged by structure modification. The objective of this work was to isolate and characterize of actinomycetes were responsibility to biosynthesis of a compound as antifungal agent and parsial identifying of these substances based on TLCbioautography. The study was done by some steps activities i.e: Isolation of actinomycete, antifungal assay, extraction and examination of MIC and TLC-bioautography using fungal test.The result of these research revealed that a genera Streptomyces spp has majority of actinomycetes was obtained from sources of microbia (decompozing sagoo solid waste). Isolate AS0827 has two a different spots which as antifungal activity based on Rf values. MIC of antifungal subtances was obtained from the actinomycetes about 200 µg/mL.The genera was shown highest of inhibition zone from of all the genera was named isolate AS0827.